Implementation of Interfaith Tolerance and Moderation in Achieving Harmony in Cisantana Village, Cigugur District, Kuningan Regency - Rahmadani, Amelia; Irawan, Rinaldi; Nadzirah, Salma; Haviz, M. (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This research discusses the importance of moderation and religious tolerance between religious communities in Indonesia, which is known for being rich in religious and cultural diversity. In the context of globalization, religious and cultural pluralism is quite a big challenge, where differences in beliefs can trigger tension and conflict if not managed well. Therefore, a religious moderation approach is proposed as a solution to overcome these differences constructively and harmoniously. The aim of this research is to explore how religious moderation can contribute to social harmony and the development of an inclusive society. This research also emphasizes the importance of tolerance as a basis for maintaining social peace, where every individual is recognized and recognized for their rights to carry out their religious beliefs. The methodology used in this research includes qualitative analysis of religious moderation practices in various communities, including in Cisantana Village, which is a clear example of how inter-religious harmony can be realized amidst diversity. The research results show that implementing an attitude of religious tolerance and moderation not only increases social unity, but also prevents conflicts that may arise due to differences in beliefs. By engaging in education, interfaith dialogue, and policies that support religious freedom, society can build mutual respect and understanding. The conclusion of this research confirms that moderation and religious tolerance are the keys to creating social harmony and preventing conflict in a multicultural society like Indonesia, as well as the importance of the active role of government and organizations in supporting these initiatives